Strategies of Transformation in Contemporary Maghrebi Cultural Narrative: Openness of Form and Experimentation through the Autobiography Chants of Salt (A Hirak Autobiography) by Larbi Ramdani as a Model - keltoum, Medakene; Messaitfa, Akila; Ilhem, Boulesnam (Journal of Ecohumanism, 2026)
The cumulative transformations within the Maghrebi reality at large, and the Algerian context specifically, have profoundly impacted literary discourse. Maghrebi cultural narrative has consequently sought to produce texts that transcend conventional constants, formal boundaries, and strict intertextuality. It achieves this by disrupting the established narrative paradigm and opening a single discourse to interacting discursive structures and other artistic mediums. Within this framework, this study examines Larbi Ramdani’s novel, Anashid al-Milh (Songs of Salt), as a text predominantly shaped by the autobiographical genre. By intersecting intertextually with various expressive forms, the novel generates a novel narrative-discursive synthesis and an unconventional structural framework. Accordingly, this study aims to reveal the primary experimental mechanisms and strategies employed by the author. Furthermore, it explores the aesthetic impact of this discursive openness within the autobiography, through the lens of literary dialogism and intertextuality, by examining the innovative artistic techniques that have reshaped the creative process."